THE COMMUNITY INVOLVEMENT IN SUSTAINING AN ARCHAEOLOGICAL SITE: THE CASE OF SARAWAK, MALAYSIA - Nur Auni, UGONG; Bilcher, BALA; Baszley Bee, BASRAH BEE; Kamaruzaman, JUSOFF (2019)
Community involvement in archaeological heritage management is the real opportunities of participation by the local community. The objective of this study was to assess the involvement of local community in preserving an archaeological site. Field visits was conducted to obtain an in-situ preservation while a face-to-face interview survey was also conducted with the local community and Sarawak Museum Staff. Their involvements to preserve the site were recorded. Results showed that community involvement plays a very important role when they were selected as site volunteers for different job specs. Collaboration between archaeologist, heritage managers and local community participation could help in preserving the sites as one of the Sarawak tourism products. Without the community involvement, the aesthetic value of the site will be destroyed or lost due to modernization. Future work should be conducted on other archaeological sites elsewhere to develop effective guidelines and policy involving local community participation.